2001
DOI: 10.1007/bf01576164
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic incisional and ventral herniorraphy: our initial 100 patients

Abstract: A review of our initial 100 patients upon whom we attempted a laparoscopic repair of either a ventral and incisional hernia is presented. The average follow-up period of these individuals was 51 months. The operation was completed with the laparoscopic technique in 96 cases. The average defect size was 155 cm2 and the average prosthetic biomaterial size to repair these defects was 214.8 cm2. The major complication rate was 4.1%. The incidence of recurrence in these patients was 9.3%. In all of these cases of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 5 publications
2
51
0
6
Order By: Relevance
“…The mesh was positioned over the defect initially with trans-parietal stitches and then fixed to the abdominal wall with spiral tacks, even though it was suggested that tacks alone allow a higher relapse rate. 17,19,20 The mesh overlapped the border of the defect by at least 3-4 cm in all the study cases. The study results showed a significant decrease in operative time.…”
Section: Discussionmentioning
confidence: 99%
“…The mesh was positioned over the defect initially with trans-parietal stitches and then fixed to the abdominal wall with spiral tacks, even though it was suggested that tacks alone allow a higher relapse rate. 17,19,20 The mesh overlapped the border of the defect by at least 3-4 cm in all the study cases. The study results showed a significant decrease in operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Übereinstimmend wird von US-amerikanischen Autoren die Bedeutung der transfaszialen Naht hervorgehoben. So beschrieben LeBlanc [7,8], LeBlanc et al [9] und Koehler et al [10], dass Rezidive in ihren Serien bei Patienten ohne Naht aufgetreten waren und folgerten, dass alle 2-3 cm eine solche Naht zusätzlich zu Spiralklammern in 1 cm Abstand erforderlich ist. Im Gegensatz dazu sind hervorragende Ergebnisse einer spanischen Serie publiziert, bei der auf jegliche Naht verzichtet wurde [11].…”
Section: Techniken Der Netzfixationunclassified
“…There are various studies going on comparing laparoscopic and open repairs and few of them suggest that recurrence rate is quite similar for both, around 9%. [9][10][11][12][13] Ventral hernia is considered complicated when it undergoes …”
Section: Introductionmentioning
confidence: 99%